A 2-(benzo[d]thiazol-2-yl)phenol based on conjugated polymer: Highly selective colorimetric fluorescent chemosensor for F-depending on Si–O bond cleavage reaction. (April 2020) - Liu, Yinhong; Wei, Yuhan; Bian, Yongshuang; He, Shengjiao; Wang, Xin; Liu, Xin; Li, Chenglei; Wu, Qi; Zeng, Xianyin; Wang, Hanguang; Liu, Kuan
Design and synthesis of highly selective fluorine ion probes become particularly important owing to the specific role of fluorine ion in chemical and biomedical progresses. As a new-type of fluorescent material, conjugated polymers with unique photometric properties have been widely researched by scientists in the field of the fluorescence sensors. In this study, the polymer PBTPV-OSi containing benzothiazole moiety is synthesized via palladium-catalyzed Heck coupling reaction. This polymer not only exhibits good solubility in organic solvents but also shows high selectivity for fluorine ion detection in comparison to other anions. Upon addition of F − to PBTPV-OSi solution, Si–O cleavage of PBTPV-OSi leads to the fluorescence quenching of the polymer in tetrahydrofuran dramatically, and the detection limit is 8 × 10 −6 mol/L. Moreover, besides detecting fluorine ion from organic phase, the probe can also effectively detect potassium fluoride from inorganic phase. More importantly, a naked-eye detectable chromogenic and fluorogenic dual response to fluorine ion (F − ) can be visibly noted and the detection process of fluorine ion is relatively fast.